Travels Between the Hudson and the Mississippi : 1851-1852 - Busch, Moritz, 1821-1899 (Book collections on Project MUSE., 1971)
Moritz Busch, a German journalist, theologian, and participant in the Revolution of 1848, proved himself both an accurate observer and a sensitive interpreter of American life in the mid-nineteenth century. His charming and richly detailed account has been translated into English for the first time. Not only an outstanding travel account, it proves to be a lode of background material that will be valued by the general reader, historians, political scientists, sociologists, and other scholars. Busch was keenly interested in the working of American institutions -- government, religion, economy, a.